2021
DOI: 10.3390/electronics10080926
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Design Alternatives for Hardware-in-the-Loop of Power Converters

Abstract: This paper aims to compare different design alternatives of hardware-in-the-loop (HIL) for emulating power converters in Field Programmable Gate Arrays (FPGAs). It proposes various numerical formats (fixed and floating-point) and different approaches (pure VHSIC Hardware Description Language (VHDL), Intellectual Properties (IPs), automated MATLAB HDL code, and High-Level Synthesis (HLS)) to design power converters. Although the proposed models are simple power electronics HIL systems, the idea can be extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…This is the minimum achievable dt with the proposed architecture based on fourth-order Runge-Kutta method, K-calculator blocks, semistep calculation during deadtimes, and the selected device. In the literature, some references can be found that reach smaller simulation steps for simple converters-such as boost and buck topologies-by using simpler methods like Euler [15,27]. However, this paper uses fourthorder Runge-Kutta which leads to a much more accurate model, as the order of the solver is O(dt 4 ), and fixes the detected issue not only for simple buck converters but to other topologies that are based on half-bridge modules.…”
Section: Synthesis Resultsmentioning
confidence: 99%
“…This is the minimum achievable dt with the proposed architecture based on fourth-order Runge-Kutta method, K-calculator blocks, semistep calculation during deadtimes, and the selected device. In the literature, some references can be found that reach smaller simulation steps for simple converters-such as boost and buck topologies-by using simpler methods like Euler [15,27]. However, this paper uses fourthorder Runge-Kutta which leads to a much more accurate model, as the order of the solver is O(dt 4 ), and fixes the detected issue not only for simple buck converters but to other topologies that are based on half-bridge modules.…”
Section: Synthesis Resultsmentioning
confidence: 99%
“…Buck converters are widely known and have been previously characterized elsewhere with and without losses [2,24,25]. To this end, different discretization methods [26] such as those of Euler [27,28], Tustin [28], zero-order hold (ZOH) [29] or Runge-Kutta [30] have been widely applied to solve the differential equations that determine the model's behavior.…”
Section: Hil Model Equationsmentioning
confidence: 99%
“…The hardware in the loop (HIL) technique has become a very popular approach for power electronics testing in recent years due to its safety and low-cost [1]. HIL allows the real-time emulation of the different parts of a system using digital hardware under non-invasive conditions [2,3]. HIL models reduce the cost of debugging, can avoid severe damages to real systems and finally reduce the overall test effort [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the recently strongly developed HiL systems, we will highlight: RTDS Technologies Inc. [12] (used, e.g., for simulation of Static VAR compensator (SVC) in a large power system [13]), Opal-RT Technologies [14] (used, e.g., for estimation of on-line parameters and current control of a six-phase induction machine [15]) and dSPACE [16] (used, e.g., for permanent magnet motors [17], and multilevel converters [18]). The FPGA-based design alternatives to HiL in power converters with different coding methods and numerical formats are compared in terms of area and speed in [19]. Another interesting approach is the proposed ultralow-latency HiL platform combining flexibility, accuracy and ease of use of state-of-the-art-simulation packages with the response speed of small powerhardware models [20].…”
Section: Introductionmentioning
confidence: 99%